Latihan Asertif Komunikasi Keluarga Bagi Warga Binaan Pemasyarakatan - Prasetiani, Abigael Grace; Andriany, Megah (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2022)
Introduction: Family communication in inmates is a problem that has not been explored much. WBP in communicating with family experiences obstacles, family communication in WBP is important to reduce the occurrence of recidivism. This study aims to determine the effectiveness of assertive training in assertive communication. Methods: The method used is a one-group test design, with a sampling technique that is purposive sampling with a sample size of 30 respondents. The data collection process is that all respondents are asked to fill out a communication questionnaire before the application intervention, namely assertive training. After being given assertive training, respondents will be given a questionnaire again. Results: The result of this application is an increase of 33% in assertive communication in WBP, and 40% of WBP need partial assistance and 40% need to be fully assisted. Discussion: Assertive training is very effective and can help improve the ability of WBP to do assertive communication, assertive communication can improve interpersonal relationships, especially with families so that divorce does not occur. In addition, assertive communication adds confidence and reduces anxiety and stress. Conclusion: Assertive training is effective for improving communication in WBP, assertive training needs to be developed further by adding monitoring and evaluation.